ANALISIS PERBANDINGAN UNJUK KERJA PROTOKOL TCP VEGAS DAN UDP DENGAN MENGGUNAKAN DATA STREAMING - Andini, Irene Rizky; Jusak, Jusak; Sukmaaji, Anjik (Journal of Control and Network Systems, 2014)
The development of an advanced technology has affected human living in the use of modern communication technology which based on data streaming. Streaming is a transmission technology of sending data, video or audio in real time or pre -recorded from the sender to the receiver. The usage of this technology is very diverse in various activities, so that the data streaming requires a rapid protocol performance in the delivery process. The final task generates comparative characteristics of TCP Vegas and UDP which based on the quality of data streaming services with the parameters of bandwidth utilization test, packet loss, latency, and jitter. The data streaming that has been used includes Voice over IP and video streaming. This comparison is performed using the network simulator 2.From the analysis that has been done, we get the value of the parameters that have been set. In general, it has been found that the percentage of bandwidth utilization on UDP protocol is larger than TCP Vegas. Then, the percentage of packet loss on TCP Vegas is higher than the UDP protocol. While, the value of a latency and jitter on TCP Vegas has a higher value than the UDP protocol.